Magnetic nanostructured based on cobalt–Zinc Ferrites designed for photocatalytic dye degradation. (March 2021) - López, J.; Ortíz, A.A.; Muñoz-Muñoz, F.; Dominguez, D.; Díaz de León, J.N.; Galindo, J.T. Elizalde; Hogan, T.; Gómez, S.; Tiznado, H.; Soto – Herrera, G.
Abstract: This work focuses on the design and manufacture of multifunctional materials for the degradation of dyes contained in effluents of the textile industry. The design is based on Co0.25 Zn0.75 Fe2 O4 ferrite nanoparticles with super-paramagnetic behavior used as seeds of the Stöber process to produce spherical SiO2 particles. The SiO2 bead works as a template where the Co0.25 Zn0.75 Fe2 O4 ferrite is mechanically stabilized to avoid particle agglomeration and the loss of the super-paramagnetic behavior. After that, the SiO2 bead is coated with ZnO ultrathin layer via an atomic layer deposition technique (ALD). The materials were characterized for morphology, size, composition, magnetic response, and photocatalytic activity using different techniques. The final Co0.25 Zn0.75 Fe2 O4 nanostructured material showed good mechanical stability, excellent magnetically response, and high efficiency in the catalytic degradation of toxic red amaranth dye under UV irradiation. The results showed that these materials are suitable to be used as efficient photocatalysts and recovered from wastewater using magnetic separation protocols. Graphical abstract: Image 1 Highlights: Co–Zn ferrite magnetic nanoparticles were synthesized and merge in SiO2 beads. Magnetic nanoparticles synthesized are considered as a soft magnetic material. ZnO layer growth by ALD on SiO2 surface, allows forming a multifunctional material. Multifunctional material was applied to photocatalytic degradation of azo dye. The multifunctional material is suitable for wastewater treatment.